Behavioral Problems in Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 1989)
Behavioral and emotional difficulties in 78 males, 6-16 years of age, with Tourette syndrome were examined at the Departments of Neurology, Pediatrics, Psychiatry, and Education at Johns Hopkins University School of Medicine and School of Continuing Studies, Baltimore, Maryland.